Improving Students’ Science Process Skills through Level of Inquiry Learning Assisted by Liveworksheet on The Concept of Environment Change - Sumiyati Sa'adah; Fadella Syifa Andini; Iwan Ridwan Yusup (Postgraduate, University of Mataram, 2024)
In the 21st century, scientific process skills are highly sought after. Interactive learning models and media can effectively train students in these skills. This research investigates the use of the Levels of Inquiry learning model assisted by Liveworksheet to improve students' science process skills in the context of environmental change. The study employs a quasi-experimental design with a non-equivalent pretest-posttest control group. Purposive sampling was used to select the participants. Data collection relied on a test sheet containing descriptive questions aligned with ten science process skill indicators. The t-test analysis (p < 0.05) revealed a significant difference in the improvement of science process skills. Notably, the increase was higher in classes utilizing the Levels of Inquiry Model with Liveworksheet compared to those without. The findings demonstrate that the Levels of Inquiry Model assisted by Liveworksheet has a significant positive impact (large effect size, d = 0.84) on developing students' science process skills when studying environmental change.